Effects of Vegetation Restoration on Soil Infiltration and Runoff in the Gully Regions on the Loess Plateau - MA Xueyan; MU Xingmin; WANG Shuangyin; BAI Yungang; NIU Fangpeng (Shuitu Baochi Xuebao)
[Objective] To study the effects of vegetation restoration on rainfall infiltration and runoff is of great theoretical and practical value for rational utilization of watershed water resources and ecological construction. [Methods] Taking the Nanxiaohegou Watershed in the Gully Region on the Loess Plateau as the research area, the double-ring infiltration experiments and slope surface simulated rainfall experiments were conducted to analyze the effects of vegetation restoration on infiltration and runoff processes and characteristics on slopes. [Results] (1) Vegetation restoration significantly increased the values of soil infiltration characteristics and capacity, with the order of artificial forest > natural grassland > corn farmland. (2) Compared to bare ground, grassland increased the transformation of rainfall into soil storage, reduced surface runoff, and led to the appearance of multiple layers of interflow. (3) Compared to bare ground, grassland showed more rapid changes in soil moisture content, richer runoff components, and less runoff volume. (4) When the intensity of rainfall on bare ground was much greater than the infiltration capacity of the land, surface runoff would be formed rapidly, and the amount of infiltration would be small, and there was a shallow and relatively impermeable layer in naturally restored grassland, and there was a big difference between the infiltration capacity of the upper and lower soil layers, so as to form a loamy mid-stream. [Conclusion] Vegetation restoration alters the hydrological properties of the soil, changing the runoff mechanism on slopes from predominantly overland flow to a combination of overland flow and interflow.